Cellulose porous structure and resin composition

By controlling the specific surface area, porosity and molecular weight of the cellulose porous structure in the mixing of cellulose porous structure and transparent resin, the problems of transparency and impact strength during mixing cellulose and resin are solved, and biological High transparency and high impact strength of degradable resins.

CN119119563APending Publication Date: 2024-12-13FUJIFILM BUSINESS INNOVATION CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410660705.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-26
Filing Date
2024-05-27
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

When existing cellulose is mixed with transparent resin, it is difficult to maintain transparency and impact strength, and the impact resistance of the biodegradable resin is low, which affects its application range.

Method used

The cellulose porous structure with a specific surface area of ​​1 m2/g or more and 150 m2/g or less and a porosity of 10% and 50% is mixed with a transparent resin, and the average diameter and number average molecular weight of the cellulose porous structure are controlled by controlling the average diameter and number average molecular weight of the cellulose porous structure. , ensure that it is evenly dispersed in the resin, and improves transparency and impact strength.

Benefits of technology

It achieves the improvement of the impact strength of the resin molded body while maintaining biodegradability and transparency, and is suitable for a variety of environments and uses.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004859487490000061
    Figure BDA0004859487490000061
  • Figure BDA0004859487490000201
    Figure BDA0004859487490000201
  • Figure BDA0004859487490000211
    Figure BDA0004859487490000211
Patent Text Reader

Abstract

Provided are: a cellulose porous structure which contains cellulose and / or a cellulose derivative as a main component, and which has a specific surface area of 1-150 m2 / g (inclusive) and a porosity of 10-50% (inclusive);
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a cellulose porous structure and a resin composition. Background Art

[0002] Patent Document 1 proposes "a method for producing a porous cellulose medium, the method comprising the steps of preparing a fluid uniform composition comprising cellulose acetate, an alkaline compound, and a solvent containing water, and gelling the composition by deacetylation of the cellulose acetate."

[0003] Patent document 2 proposes "a particle containing cellulose acetate, wherein the average particle size of the particles is 80 nm or more and 100 μm or less, the sphericity is 0.7 or more and 1.0 or less, the surface smoothness is 80% or more and 100% or less, and the surface contact angle with respect to water is 100° or more, and the total acetyl substitution degree of the cellulose acetate is 0.7 or more and 2.9 or less."

[0004] Patent document 3 proposes "a polylactic acid-based resin composition, characterized in that it is composed of a polymer component (A) containing polylactic acid (a1) and an aliphatic polyester (a2) having a melting point of 50 to 250°C and being biodegradable, wherein, based on the total weight of the polylactic acid (a1) and the aliphatic polyester (a2), it contains 90 to 50% by weight of the polylactic acid (a1) and 10 to 50% by weight of the aliphatic polyester (a2), and the biodegradable natural product (B) contains 0.1 to 100 parts by weight relative to 100 parts by weight of the polymer component (A)".

[0005] Patent Document 1: International Publication No. 2016 / 159334

[0006] Patent Document 2: International Publication No. 2020 / 188698

[0007] Patent Document 3: Japanese Patent Application Laid-Open No. 11-241009 Summary of the invention

[0008] The present invention aims to provide a cellulose porous structure comprising at least one of cellulose and a cellulose derivative as a main component, wherein the cellulose porous structure has a specific surface area of ​​less than 1 m 2 / g or more than 150m 2 / g, or a porosity of less than 10% or more than 50%, a resin molded body having high transparency and impact strength can be obtained.

[0009] Means for solving the above-mentioned problems include the following aspects.

[0010] <1>

[0011] A cellulose porous structure comprising at least one of cellulose and a cellulose derivative as a main component,

[0012] The specific surface area is 1m 2 / g and above and 150m 2 / g or less,

[0013] The porosity is 10% or more and 50% or less.

[0014] <2>

[0015] The porous cellulose structure according to <1>, wherein when the porous cellulose structure and a resin are kneaded, the porous cellulose structure is present in the resin with an average diameter of 50 μm or less.

[0016] <3>

[0017] The porous cellulose structure according to <1> or <2>, wherein the cellulose and the cellulose derivative have a number average molecular weight of 15,000 or more.

[0018] <4>

[0019] The porous cellulose structure according to any one of <1> to <3>, wherein the cellulose derivative is cellulose acetate.

[0020] <5>

[0021] A resin composition comprising a kneaded product containing a transparent resin and the cellulose porous structure according to any one of <1> to <4>.

[0022] <6>

[0023] The resin composition according to <5>, wherein a molded body of the resin composition has a haze value of 15% or less when the thickness of the molded body is 2 mm.

[0024] <7>

[0025] The resin composition according to <5> or <6>, wherein the Charpy impact strength is 2.5 kJ / m 2 above.

[0026] Effects of the Invention

[0027] According to the invention described in <1>, there is provided a cellulose porous structure comprising at least one of cellulose and a cellulose derivative as a main component, wherein the cellulose porous structure has a specific surface area of ​​less than 1 m 2 / g or more than 150m 2 / g, or a porosity of less than 10% or more than 50%, a resin molded body having high transparency and impact strength can be obtained.

[0028] According to the invention of <2>, there is provided a cellulose porous structure which can obtain a resin molded body having high transparency and impact strength compared with a case where the cellulose porous structure exists in the resin with an average diameter exceeding 50 μm when the cellulose porous structure and the resin are kneaded.

[0029] According to the invention as set forth in <3>, there is provided a cellulose porous structure capable of obtaining a resin molded body having high transparency and impact strength compared to a case where the number average molecular weight of cellulose or a cellulose derivative is less than 15,000.

[0030] According to the invention as set forth in <4>, there is provided a cellulose porous structure capable of obtaining a resin molded body having higher biodegradability, transparency and impact strength than when the cellulose derivative is cellulose acetate propionate.

[0031] According to the invention of <5>, <6> or <7>, there is provided a resin composition comprising a kneaded product comprising a transparent resin and a cellulose porous structure containing at least one of cellulose and a cellulose derivative as a main component, and a resin composition having a specific surface area of ​​less than 1 m 2 / g or more than 150m 2 / g, or a cellulose porous structure having a porosity of less than 10% or more than 50%, a resin molded body having high transparency and impact strength can be obtained. DETAILED DESCRIPTION

[0032] Hereinafter, an embodiment as an example of the present invention will be described. These descriptions and examples are for illustrative purposes only and do not limit the scope of the invention.

[0033] In the numerical ranges described in this specification, the upper limit or lower limit described in one numerical range can be replaced by the upper limit or lower limit of the numerical range described in another stage. In addition, in the numerical ranges described in this specification, the upper limit or lower limit of the numerical range can be replaced by the value shown in the examples.

[0034] Each component may contain a plurality of corresponding substances.

[0035] When referring to the amount of each component in a composition, if there are plural substances corresponding to each component in the composition, unless otherwise specifically stated, the amount refers to the total amount of the plural substances present in the composition.

[0036] <Cellulose porous structure>

[0037] The cellulose porous structure according to the present embodiment contains at least one of cellulose and a cellulose derivative as a main component and has a specific surface area of ​​1 m 2 / g and above and 150m 2 / g or less, and a porosity of 10% to 50%.

[0038] The cellulose porous structure according to the present embodiment is, for example, a powder containing at least one of cellulose and a cellulose derivative as a main component.

[0039] The porous cellulose structure according to the present embodiment can obtain a resin molded body having high transparency and impact strength due to the above-mentioned structure. The reason for this is presumably as follows.

[0040] Cellulose structures mainly composed of cellulose and cellulose derivatives are rapidly biodegradable in any environment such as compost, activated sludge, or seawater, and are being put to practical use in a variety of applications.

[0041] One of its uses is as a modifier for improving impact strength.

[0042] However, when a cellulose structure is kneaded with a transparent resin, the transparency of the obtained resin composition (ie, a resin molded product obtained from the resin composition) may be reduced. This is considered to be because the cellulose structure is difficult to finely disperse in the transparent resin and has low dispersibility.

[0043] Furthermore, higher impact strength based on the cellulose structure is also required.

[0044] In contrast, the cellulose porous structure having the above-mentioned specific surface area and porosity has easy disintegration. Thus, if the cellulose porous structure is kneaded with a transparent resin, the cellulose porous structure will disintegrate and be dispersed in the transparent resin in a nearly fine and uniform state. Therefore, the transparency of the transparent resin can be suppressed from decreasing, and the original transparency of the transparent resin can be easily maintained.

[0045] On the other hand, by dispersing the cellulose porous structure in the transparent resin in a nearly fine and uniform state, the crystallization of the transparent resin is improved. In addition, it is considered that the porous structure of the cellulose porous structure increases the contact points between the cellulose porous structure and the transparent resin, and the modification ability of the cellulose porous structure is improved, so that the impact resistance of the transparent resin is improved.

[0046] Furthermore, in order to show the transparency of the transparent resin, for example, the added cellulose structure is preferably dispersed in a small size and nearly uniformly. For example, there are already cellulose structures with smaller sizes such as cellulose nanofibers, but because they have high hydrogen bonding properties, when added to the transparent resin by kneading, they are prone to secondary aggregation and become larger in size, so the transparency of the transparent resin is greatly reduced. On the other hand, it is considered as follows: the cellulose porous structure involved in this embodiment is not easy to cause secondary aggregation in the resin by being crushed by kneading torque, and can be evenly dispersed in a small size, so it can show high transparency.

[0047] And, regarding impact strength, for example, in addition to being nearly uniformly dispersed, it is preferred to improve adhesion (i.e., contact area) with transparent resin. The cellulose porous structure involved in the present embodiment can be dispersed in transparent resin while being crushed by kneading as described above, so the crushed surface is irregular, and the contact area with transparent resin can be increased. Therefore, high impact strength can be obtained.

[0048] Based on the above, it is presumed that the porous cellulose structure according to the present embodiment can obtain a resin molded body having high transparency and impact strength due to the above structure.

[0049] In recent years, due to environmental awareness represented by SDGs (Sustainable Development Goals), interest in biomass resins or biodegradable resins has been increasing. In particular, among biomass resins and biodegradable resins, polylactic acid is a carbon-neutral, highly biodegradable resin and is highly anticipated as a substitute for petroleum-derived plastics. However, biomass resins and biodegradable resins, especially polylactic acid, have low impact resistance and their uses are limited.

[0050] If petroleum-based resins and modifiers are compounded in biomass resins and biodegradable resins, impact resistance can be improved, but this will reduce biomass, CO2 emissions, petroleum resources, and other environmental effects. In addition, when the biomass resin and biodegradable resin are transparent resins (especially polylactic acid), the modifier will damage the original transparency of the resin.

[0051] However, if the cellulose porous structure according to the present embodiment is used, even if a biomass resin or a biodegradable resin is used as the transparent resin, a resin molded body having high biomass or biodegradability and high transparency and impact strength can be obtained.

[0052] In addition, for example, the following is reported: excellent molding processability, strength and flexibility are obtained while maintaining high biomass by using biodegradable resin and cellulose particles with a sphericity of 0.9 or more. However, since the specific surface area of ​​cellulose particles is small, a large amount of addition is required to express the effect, which hinders the original transparency and impact resistance of the biodegradable resin.

[0053] In addition, for example, it is reported that a resin composition composed of polylactic acid, a biodegradable polyester having a melting point of 50°C or more and 250°C or less, and a natural product improves the biodegradation rate while maintaining the characteristics of polylactic acid (for example, Patent Document 3). However, aliphatic polyester is not a biomass resin, so the biomass is reduced. In addition, the particle size of the natural product is large, the contact area with the resin is small, and the compatibility of polylactic acid and aliphatic polyester is low, forming an island region, so it is difficult to disperse finely, and thus the impact resistance is low.

[0054] Hereinafter, the porous cellulose structure according to the present embodiment will be described in detail.

[0055] (Cellulose and cellulose derivatives)

[0056] The cellulose porous structure according to the present embodiment contains, for example, at least one of cellulose and a cellulose derivative as a main component.

[0057] Here, "comprising at least one of cellulose and a cellulose derivative as a main component" means that the total content of cellulose and the cellulose derivative relative to the cellulose porous structure is 90 mass % or more, for example, preferably 95 mass % or more, 98 mass % or more, or 100 mass %.

[0058] Cellulose is a polymer compound formed by linear polymerization of multiple β-glucose molecules through glycosidic bonds.

[0059] On the other hand, examples of cellulose derivatives include cellulose acylate, cellulose ether, hydroxyalkyl cellulose, and carboxymethyl cellulose.

[0060] Among them, as the cellulose derivative, for example, cellulose acylate is preferred from the viewpoint of high biodegradability.

[0061] Cellulose acylate is a cellulose derivative in which at least a part of the hydroxyl groups in cellulose is substituted (acylated) by acyl groups. AC (R AC represents a hydrogen atom or a hydrocarbon group. ) structure group.

[0062] Cellulose acylate is, for example, a cellulose derivative represented by the following general formula (CA).

[0063] [Chemical formula 1]

[0064]

[0065] In the general formula (CA), A 1 , A 2 and A 3 Each independently represents a hydrogen atom or an acyl group, and n represents an integer greater than 2. 1 、nA 2 and n A 3 At least one of the A represents an acyl group. 1 They may be all the same, partly the same, or different from each other. 2 And there are n A 3 They may be entirely the same, partially the same, or different from each other.

[0066] In A 1 , A 2 and A 3 In the acyl group represented, the hydrocarbon group in the acyl group may be any of linear, branched, and cyclic, and is preferably linear or branched, and more preferably linear.

[0067] In A 1 , A 2 and A 3 In the acyl group represented, the hydrocarbon group in the acyl group may be a saturated hydrocarbon group or an unsaturated hydrocarbon group, and for example, a saturated hydrocarbon group is more preferable.

[0068] A 1 , A 2 and A 3 The acyl group represented is preferably an acyl group having, for example, 1 to 6 carbon atoms. That is, as cellulose acylate, for example, a cellulose acylate having 1 to 6 carbon atoms in the acyl group is preferred.

[0069] A 1 , A 2 and A 3 The acyl group represented may be a group in which a hydrogen atom in the acyl group is substituted with a halogen atom (eg, a fluorine atom, a bromine atom, an iodine atom), an oxygen atom, a nitrogen atom or the like, but is preferably an unsubstituted group.

[0070] As A 1 , A 2 and A 3Examples of the acyl group include formyl, acetyl, propionyl, butanoyl, acryloyl, hexanoyl, etc. Among them, as the acyl group, from the viewpoint of increasing the biodegradation rate of the resin particles, for example, an acyl group having 2 to 4 carbon atoms is more preferred, and an acyl group having 2 or 3 carbon atoms is further preferred.

[0071] Examples of cellulose acylate include cellulose acetate (monoacetate cellulose, diacetate cellulose (DAC), triacetate cellulose), cellulose acetate propionate (CAP), and cellulose acetate butyrate (CAB).

[0072] From the viewpoint of high biodegradability, cellulose acylate is preferably cellulose acetate, for example.

[0073] From the viewpoint of biodegradability, the degree of substitution of cellulose acylate is, for example, preferably 1.7 to 2.9, more preferably 1.9 to 2.6, further preferably 2.0 to 2.5, particularly preferably 2.1 to 2.4.

[0074] The degree of substitution of cellulose acylate is an index indicating the degree to which the hydroxyl groups of cellulose are replaced by acyl groups. That is, the degree of substitution is an index indicating the degree of acylation of cellulose acylate. Specifically, the degree of substitution indicates the intramolecular average of the number of substitutions of 3 hydroxyl groups in the D-pyranose glucose unit of cellulose acylate by acyl groups. 1 H-NMR (manufactured by JMN-ECA / JEOL RESONANCE Inc.) was determined from the integrated ratio of the peaks of hydrogen derived from cellulose and hydrogen derived from acyl groups.

[0075] These cellulose derivatives may be used alone or in combination of two or more.

[0076] -Number average molecular weight of cellulose and cellulose derivatives-

[0077] The number average molecular weight of cellulose and cellulose derivatives is, for example, preferably 5,000 or more, more preferably 10,000 or more, and even more preferably 15,000 or more.

[0078] If the number average molecular weight of cellulose and cellulose derivatives is within the above range, the cellulose porous structure can be prevented from being finely disintegrated before being kneaded with the resin. As a result, secondary aggregation after disintegration can be suppressed, and nearly fine and uniform dispersion in the resin can be easily achieved, which can easily improve the transparency and impact resistance of the resin molded body.

[0079] Among them, from the viewpoint of suppressing a decrease in biodegradability, the number average molecular weight of cellulose and a cellulose derivative is, for example, preferably 50,000 or less, and more preferably 30,000 or less.

[0080] The number average molecular weight of cellulose and cellulose derivatives was measured by gel permeation chromatography (differential refractometer Optilab T-rEX / manufactured by Wyatt Technology Corporation, multi-angle light scattering detector DAWN HELEOSII / manufactured by Wyatt Technology Corporation, columns TSKgel α-M and α-3000, 1 each / manufactured by TOSOH CORPORATION) using dimethylacetamide (with 0.1 M lithium chloride added) as solvent.

[0081] (Other ingredients)

[0082] The porous cellulose structure according to the present embodiment may contain other components.

[0083] (Characteristics of Cellulose Porous Structure)

[0084] -Specific surface area-

[0085] The specific surface area of ​​the porous cellulose structure according to this embodiment is 1 m 2 / g and above and 150m 2 / g or less, for example, preferably 10m 2 / g and above and 150m 2 / g or less, more preferably 20m 2 / g or more and 100m 2 / g or less.

[0086] If the specific surface area of ​​the cellulose porous structure is 1m 2 / g or more, the modification ability of the cellulose porous structure can be fully exerted to improve the impact resistance.

[0087] If the specific surface area of ​​the cellulose porous structure is 150 m 2 / g or less, the cellulose porous structure can be prevented from being crushed before being kneaded with the resin. As a result, secondary aggregation after crushing can be suppressed, and nearly fine and uniform dispersion in the resin can be achieved, thereby improving the transparency and impact resistance of the resin molded body.

[0088] The specific surface area of ​​the cellulose porous structure is a BET specific surface area, and is a value measured by automatic measurement using a specific surface area / pore size distribution measuring device (BELSORP MAXII MicrotracBEL Corp.) by a multi-point method. The measurement temperature was set to 77 K, and nitrogen was used as the adsorption gas.

[0089] Prior to the measurement, the sample (ie, the cellulose porous structure) was vacuum dried at 100° C. for 24 hours as a pretreatment to remove water adsorbed in the pores of the sample.

[0090] -Porosity-

[0091] The porosity of the porous cellulose structure according to the present embodiment is 10% to 50%, for example, preferably 15% to 50%, and more preferably 20% to 50%.

[0092] When the porosity of the porous cellulose structure is 10% or more, the modification ability of the porous cellulose structure is fully exerted, and the impact resistance is improved.

[0093] If the porosity of the cellulose porous structure is 50% or less, the cellulose porous structure can be prevented from being crushed before being kneaded with the resin. As a result, secondary aggregation after crushing can be suppressed, and a nearly fine and uniform dispersion in the resin can be achieved, thereby improving the transparency and impact resistance of the resin molded body.

[0094] The porosity of the porous cellulose structure is measured as follows.

[0095] The cellulose porous structure was observed by scanning electron microscopy (SEM) at a magnification of 25,000 times, and a SEM image was obtained. The SEM image was read into the image processing software "ImageJ" and binarized to obtain the overall area of ​​the cellulose porous structure and the pores. Then, the ratio of the pores of the cellulose porous structure to the overall area of ​​the cellulose porous structure was obtained to obtain the porosity of the cellulose porous structure.

[0096] This operation was performed 10 times, and the average value was calculated.

[0097] -Average diameter-

[0098] The average diameter of the porous cellulose structure is, for example, preferably 1 μm or more and 500 μm or less, more preferably 1 μm or more and 355 μm or less, and further preferably 1 μm or more and 150 μm or less.

[0099] When the average diameter of the porous cellulose structure is 1 μm or more, the porous cellulose structure will collapse when kneading the porous cellulose structure with a resin, and can be easily dispersed in the resin in a nearly fine and uniform manner, thereby improving the transparency and impact resistance of the resin molded body.

[0100] If the average diameter of the cellulose porous structure is 500 μm or less, the cellulose porous structure can be prevented from being crushed before being kneaded with the resin. As a result, secondary aggregation after crushing can be suppressed, and a nearly fine and uniform dispersion in the resin can be easily achieved, thereby improving the transparency and impact resistance of the resin molded body.

[0101] The method for measuring the average diameter of the cellulose porous structure is as follows.

[0102] The cellulose porous structure was observed by scanning electron microscopy (SEM) at a magnification of 250 times, and a SEM image was obtained. The SEM image was read into the image processing software "ImageJ", and the circle equivalent diameter was calculated based on the area of ​​the cellulose porous structure. Then, the average value of the circle equivalent diameters of 20 cellulose porous structures was calculated and used as the average diameter.

[0103] -Average Diameter of Cellulose Porous Structure in Resin-

[0104] In the cellulose porous structure involved in this embodiment, when the cellulose porous structure is mixed with a resin, the cellulose porous structure preferably exists in the resin with an average diameter of less than 50 μm, more preferably with an average diameter of less than 10 μm, and further preferably with an average diameter of less than 1 μm.

[0105] When the cellulose porous structure is present in the resin with an average diameter of 50 μm or less, it is finely dispersed in the resin, thereby improving the transparency and impact resistance of the resin molded body.

[0106] Furthermore, from the viewpoint of fully utilizing the modifying ability of the cellulose resin to improve the impact resistance of the resin molded body, when the cellulose porous structure and the resin are kneaded, the cellulose porous structure preferably exists in the resin with an average diameter of, for example, 0.05 μm or more.

[0107] The average diameter of the cellulose porous structure in the resin is the average diameter of the cellulose porous structure when the cellulose porous structure and the resin are kneaded under the conditions of "Example 1" described later. Then, the average diameter of the cellulose porous structure is measured as follows.

[0108] The resin composition obtained by mixing the cellulose porous structure with the resin is cut. The cellulose porous structure of the cut surface of the resin composition is observed at a magnification of 1000 times by a scanning electron microscope (SEM), and a SEM image is obtained. The SEM image is read into the image processing software "ImageJ", and the circle equivalent diameter is obtained according to the area of ​​the cellulose porous structure. Then, the average value of the circle equivalent diameters of 20 cellulose porous structures is obtained, and it is used as the average diameter.

[0109] -proportion-

[0110] The specific gravity of the porous cellulose structure according to the present embodiment is preferably, for example, 0.5 g / cm 3 Above and 1.15g / cm 3 Below, more preferably 0.60g / cm 3 Above and 1.0g / cm 3 Below, more preferably 0.70 g / cm 3 Above and 0.90g / cm 3 the following.

[0111] When the specific gravity of the porous cellulose structure is within the above range, the porous cellulose structure can be easily dispersed in the resin in a nearly fine and uniform manner when kneading the porous cellulose structure with the resin, thereby improving the transparency and impact resistance of the resin molded product.

[0112] The method for measuring the specific gravity of the cellulose porous structure is as follows.

[0113] 30 g of the structure was used as a sample and an automatic specific gravity meter (DSG-1 manufactured by Toyo Seiki Seisaku-sho, Ltd.) was used. The measurement was performed three times by a water substitution method except that the measurement liquid was changed from water to ethanol. The average of the results was taken as the measured value.

[0114] (Method for producing porous cellulose structure)

[0115] The porous cellulose structure according to the present embodiment can be obtained, for example, by the following method.

[0116] (1) A cellulose derivative is added to a good solvent for the cellulose derivative, and then heated to obtain a solution A in which the cellulose derivative is dissolved in the good solvent.

[0117] (2) A poor solvent for the cellulose derivative is added to solution A to obtain solution B.

[0118] (3) Solution B is rapidly cooled to generate a gel-like substance of the cellulose derivative by phase separation.

[0119] (4) After washing the gel-like substance, drying is performed to obtain a cellulose porous structure having a cellulose derivative as a main component.

[0120] (5) The obtained cellulose porous structure can be crushed and sieved to remove coarse particles and agglomerates as needed. The crushing method is not particularly limited, and can be carried out, for example, by a dry pulverizing device such as a jet mill, a vibration mill, a ball mill, or a pin mill. The sieving method can be carried out, for example, by a known method such as a vibrating screen or a wind-powered sieving machine.

[0121] Here, by saponifying the gel-like substance (that is, by saponifying the cellulose derivative), cellulose or a cellulose porous structure containing cellulose and a cellulose derivative as a main component is obtained depending on the degree of saponification.

[0122] <Resin composition>

[0123] The resin composition according to the present embodiment is a resin composition composed of a kneaded product containing a transparent resin and the cellulose porous structure according to the present embodiment.

[0124] Specifically, the resin composition according to the present embodiment includes a transparent resin and a disintegrated product obtained by disintegrating the cellulose porous structure according to the present embodiment through kneading with the transparent resin.

[0125] (Transparent resin)

[0126] The transparent resin is a resin having a haze value of 15% or less when a molded body of the transparent resin alone has a thickness of 2 mm.

[0127] Examples of the transparent resin include styrenes (e.g., styrene, p-chlorostyrene, α-methylstyrene, etc.), (meth)acrylates (e.g., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (e.g., acrylonitrile, methacrylonitrile, etc.), vinyl ethers (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), olefins (e.g., ethylene, propylene, butadiene, etc.), vinyl alcohol and other monomers, homopolymers thereof, or copolymers obtained by combining two or more of these monomers, and amorphous polyolefins.

[0128] Examples of the transparent resin include non-vinyl resins such as polyester resins, epoxy resins, polyurethane resins, polyamide resins, polyether resins, and modified rosin, and mixtures thereof with the above-mentioned vinyl resins, or graft polymers obtained by polymerizing vinyl monomers under conditions where the above-mentioned resins coexist.

[0129] Examples of the transparent resin include natural polymers and the like.

[0130] Here, examples of the polyester resin include aliphatic polyester resins, aliphatic aromatic polyester resins, and the like.

[0131] Examples of the aliphatic polyester resin include polylactic acid (PLA), polyglycolic acid (PGA), polyhydroxyalkanoate (PHA), polycaprolactone, polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), polybutylene adipate (PBA) and other polyhydroxyalkanoic acids.

[0132] Examples of the aliphatic aromatic polyester resin include polyadipate / butylene terephthalate copolymer resin (PBAT) and polyadipate / tetramethylene terephthalate copolymer resin.

[0133] Examples of the natural polymer include starch, cellulose, chitin, chitosan, gluten, gelatin, zein, soybean protein, collagen, and keratin.

[0134] Examples of the biodegradable resin include cellulose derivatives (cellulose acylate, cellulose ether, hydroxyalkyl cellulose, and carboxymethyl cellulose).

[0135] Among these transparent resins, from the viewpoint of environmental compatibility, examples of the transparent resin include biomass resins and biodegradable resins, and particularly preferred are resins corresponding to both biomass resins and biodegradable resins (particularly preferred is polylactic acid).

[0136] The biodegradable resin is a resin other than cellulose that is decomposed into water and carbon dioxide by microorganisms. Specifically, in the present embodiment, the biodegradable resin means a resin having a biodegradability of 5% or more under aerobic conditions within 28 days as measured by the method according to ISO 14855-1:2012.

[0137] These transparent resins may be used alone or in combination of two or more.

[0138] The content of the transparent resin is, for example, preferably 90% by mass or more and 99.9% by mass or less, and more preferably 95% by mass or more and 99.9% by mass or less, based on the resin composition.

[0139] (Content of Cellulose Porous Structure)

[0140] The content of the cellulose porous structure is, for example, preferably 0.1% by mass to 20% by mass, more preferably 1% by mass to 10% by mass, and even more preferably 1% by mass to 5% by mass, based on the transparent resin.

[0141] When the content of the porous cellulose structure is within the above range, a resin molded body having sufficiently high transparency and impact resistance can be easily obtained.

[0142] (Other ingredients)

[0143] The resin composition according to this embodiment may contain other components.

[0144] Examples of other components include plasticizers, flame retardants, compatibilizers, release agents, lightfast agents, weatherproof agents, colorants, pigments, modifiers, anti-dripping agents, antistatic agents, hydrolysis inhibitors, fillers, reinforcing agents (glass fiber, carbon fiber, talc, clay, mica, glass flakes, ground glass, glass beads, crystalline silica, alumina, silicon nitride, aluminum nitride, boron nitride, etc.), acid acceptors (oxides such as magnesium oxide and aluminum oxide; metal hydroxides such as magnesium hydroxide, calcium hydroxide, aluminum hydroxide, and hydrotalcite; calcium carbonate; talc; etc.), reactive scavengers (for example, epoxy compounds, acid anhydride compounds, carbodiimide, etc.), and the like.

[0145] The content of other components is preferably 0% by mass or more and 5% by mass or less, respectively, based on the total amount of the resin composition. Here, "0% by mass" means that other components are not included.

[0146] (Characteristics of resin composition)

[0147] -Average Diameter of Cellulose Porous Structure in Transparent Resin-

[0148] In the resin composition involved in the present embodiment, the cellulose porous structure (i.e., the disintegrated product of the cellulose porous structure involved in the present embodiment mentioned above) is preferably present in an average diameter of less than 50 μm, more preferably less than 10 μm, and further preferably less than 1 μm in a transparent resin.

[0149] When the cellulose porous structure is present in a transparent resin with an average diameter of 50 μm or less, the structure is finely dispersed in the resin, thereby improving the transparency and impact resistance of the resin composition.

[0150] The average diameter of the cellulose porous structure in the transparent resin is measured as follows.

[0151] Cut the resin composition. Observe the cellulose porous structure of the cut surface of the resin composition at a magnification of 1000 times by a scanning electron microscope (SEM), and obtain a SEM image. The SEM image is read into the image processing software "ImageJ", and the circle equivalent diameter is calculated based on the area of ​​the cellulose porous structure. Then, the average value of the circle equivalent diameters of 20 cellulose porous structures is calculated and used as the average diameter.

[0152] -Haze value-

[0153] In the resin composition according to the present embodiment, the haze value of a molded body of the resin composition when the thickness is 2 mm is, for example, preferably 15% or less, more preferably 10% or less, and further preferably 7% or less. The haze value is ideally 0%.

[0154] When the haze value is within the above range, a resin molded product having sufficiently high transparency can be obtained.

[0155] (Charpy impact strength)

[0156] The Charpy impact strength of the resin composition according to the present embodiment is preferably, for example, 1 kJ / m 2 More preferably, 2 kJ / m 2 More preferably, 2.5 kJ / m 2 Above, especially preferably 3 kJ / m 2 Above, most preferably 4 kJ / m 2 above.

[0157] When the Charpy impact strength is within the above range, a resin molded body having sufficiently high impact resistance can be easily obtained.

[0158] Here, the haze value and the Charpy impact strength are values ​​measured by the methods described in the “Examples” described later.

[0159] (Method for producing resin composition)

[0160] As the manufacturing method of the resin composition involved in the present embodiment, for example, a method of mixing the components and performing melt kneading, etc. can be cited. As the mechanism of melt kneading, there is no particular limitation, and for example, a twin-screw extruder, a Henschel mixer, a Banbury mixer, a single-screw extruder, a multi-screw extruder, a kneader, etc. can be cited.

[0161] Then, by controlling the kneading conditions, it is possible to obtain a resin composition including a transparent resin and a disintegrated product in which the porous cellulose structure according to the present embodiment is disintegrated by kneading with the transparent resin.

[0162] <Resin molded body>

[0163] The resin molded body according to the present embodiment includes the resin composition according to the present embodiment. That is, the resin molded body according to the present embodiment is composed of the same combination as the resin composition according to the present embodiment.

[0164] As a molding method of the resin molded article according to the present embodiment, an injection molded article obtained by injection molding can be mentioned from the viewpoint of high degree of freedom in shape.

[0165] The injection molding of the resin molded body according to the present embodiment can be performed using commercially available apparatuses such as NEX500 manufactured by NISSEI PLASTIC INDUSTRIAL CO., LTD., NEX150 manufactured by NISSEI PASTIC INDUSTRIAL CO., LTD., NEX7000 manufactured by NISSEI PASTIC INDUSTRIAL CO., LTD., PNX40 manufactured by NISSEI PASTIC INDUSTRIAL CO., LTD., and SE50D manufactured by Sumitomo Heavy Industries, Ltd.

[0166] The resin molded body of the present embodiment may be a resin molded body obtained by other molding methods, such as extrusion molding, blow molding, hot press molding, calendering molding, coating molding, casting molding, impregnation molding, vacuum molding, transfer molding, etc.

[0167] Examples of uses of the resin molded body according to the present embodiment include frames of electronic / electrical equipment or household appliances; various components of electronic / electrical equipment or household appliances; interior components of automobiles; building block assembly toys; plastic model kits; storage boxes for CD-ROMs or DVDs; tableware; beverage bottles; food trays; packaging materials; films; sheets, etc.

[0168] Example

[0169] Hereinafter, examples will be described, but the present invention is not limited to these examples. In the following description, "parts" and "%" are based on mass unless otherwise specified.

[0170] <Production of Cellulose Porous Structure>

[0171] (Cellulose porous structure CPS (1))

[0172] In a container, 5 parts by mass of cellulose acetate DAC (1) was added to 20 parts by mass of dimethylformamide to obtain a solution A, which was stirred at 90°C for 1 hour. After dissolving cellulose acetate in dimethylformamide in solution A, 25 parts by mass of hexanol were slowly added to solution A while stirring, and the obtained solution B was stirred for 1 hour. Then, solution B was immersed in ice water together with the container for rapid cooling, and a gel product of a cellulose porous structure was obtained by phase separation. The generated gel product was washed with 200 parts by mass of ethanol and vacuum dried at 50°C for 24 hours to obtain a cellulose porous structure. Then, the structure was crushed with a grinder and sieved with a 106 μm mesh to obtain a finely pulverized cellulose structure.

[0173] (Cellulose porous structure CPS (2))

[0174] A cellulose porous structure CPS (2) was obtained in the same manner as in the cellulose porous structure CPS (1) except that the mesh diameter of the sieve was set to 53 μm.

[0175] (Cellulose porous structure CPS (3))

[0176] A cellulose porous structure CPS (3) was obtained in the same manner as in the cellulose porous structure CPS (1) except that the amount of cellulose acetate DAC (1) was changed to 7.5 parts by mass.

[0177] (Cellulose porous structure CPS (4))

[0178] A cellulose porous structure CPS (4) was obtained in the same manner as in the cellulose porous structure CPS (1) except that the amount of cellulose acetate DAC (1) was changed to 3.5 parts by mass.

[0179] (Cellulose porous structure CPS (5))

[0180] A cellulose porous structure CPS (5) was obtained in the same manner as the cellulose porous structure CPS (1) except that cellulose acetate DAC (1) was changed to DAC (2).

[0181] (Cellulose porous structure CPS (6))

[0182] A cellulose porous structure CPS (6) was obtained in the same manner as the cellulose porous structure CPS (1) except that cellulose acetate DAC (1) was changed to DAC (3).

[0183] (Cellulose porous structure CPS (7))

[0184] A cellulose porous structure CPS (7) was obtained in the same manner as the cellulose porous structure CPS (1) except that cellulose acetate DAC (1) was changed to DAC (4).

[0185] (Cellulose porous structure CPS (8))

[0186] A cellulose porous structure CPS (8) was obtained in the same manner as in the cellulose porous structure CPS (1) except that cellulose acetate was changed to triacetyl cellulose.

[0187] (Cellulose porous structure CPS (9))

[0188] A cellulose porous structure CPS (9) was obtained in the same manner as in the cellulose porous structure CPS (1) except that cellulose acetate was changed to cellulose acetate propionate.

[0189] (Cellulose porous structure CPS (10))

[0190] A cellulose porous structure CPS (10) was obtained in the same manner as the cellulose porous structure CPS (1) except that cellulose acetate was changed to cellulose acetate butyrate.

[0191] (Cellulose porous structure CPS (11))

[0192] A cellulose porous structure CPS (11) was obtained in the same manner as the cellulose porous structure CPS (1), except that alkali saponification was performed before the gel product was washed with ethanol.

[0193] (Cellulose porous structure CPS (12))

[0194] A cellulose porous structure CPS (12) was obtained in the same manner as the cellulose porous structure CPS (1) except that the mesh diameter of the sieve was set to 500 μm.

[0195] (Cellulose porous structure CPS (13))

[0196] A cellulose porous structure CPS (13) was obtained in the same manner as in the cellulose porous structure CPS (1) except that the amount of cellulose acetate was changed to 12.5 parts by mass.

[0197] (Cellulose porous structure CPS (14))

[0198] A cellulose porous structure CPS (14) was obtained in the same manner as the cellulose porous structure CPS (1) except that cellulose acetate DAC (1) was changed to DAC (5).

[0199] (Cellulose porous structure CPS (15))

[0200] A cellulose porous structure CPS (15) was obtained in the same manner as the cellulose porous structure CPS (1) except that the sieving step was not performed.

[0201] (Cellulose porous structure CPS (16))

[0202] A porous cellulose structure CPS (16) was obtained in the same manner as in the porous cellulose structure CPS (1) except that dimethylformamide was changed to 180 parts by mass and hexanol was changed to 450 parts by mass.

[0203] (Cellulose porous structure CPS (17))

[0204] A porous cellulose structure CPS (17) was obtained in the same manner as in the porous cellulose structure CPS (1) except that the amount of cellulose acetate was changed to 15 parts by mass.

[0205] (Cellulose porous structure CPS (18))

[0206] A cellulose porous structure CPS (1) was obtained in the same manner as the cellulose porous structure CPS (1) except that dimethylformamide was changed to 180 parts by mass and hexanol was changed to 450 parts by mass.

[0207] (Cellulose porous structure CPS (C1))

[0208] Cellulose acetate DAC (1) was crushed with a grinder and then sieved with a 106 μm sieve to obtain a cellulose structure (C1).

[0209] (Cellulose porous structure CPS (C2))

[0210] 130 parts by mass of cellulose acetate DAC (1) was dissolved in 870 parts by mass of ethyl acetate. This was added to a dispersion obtained by dispersing 50 parts by mass of calcium carbonate in 500 parts by mass of pure water, and stirred for 3 hours. This was added to a dispersion obtained by dispersing 4 parts by mass of carboxymethyl cellulose and 200 parts by mass of methyl ethyl ketone in 600 parts by mass of pure water, and stirred for 5 minutes using a high-speed emulsifier. 10 g of sodium hydroxide was added thereto, and the mixture was stirred at 80° C. for 3 hours to remove ethyl acetate and methyl ethyl ketone. 10 g of dilute hydrochloric acid was added thereto, and the residue was filtered to obtain non-porous cellulose particles.

[0211] (Characteristics of Cellulose Porous Structure)

[0212] The following properties of the obtained cellulose porous structure were measured according to the methods described above.

[0213] Average diameter of cellulose porous structure

[0214] ·Specific surface area of ​​cellulose porous structure (marked as "BET" in the table)

[0215] Porosity of cellulose porous structure

[0216] Specific gravity of cellulose porous structure

[0217] When the cellulose porous structure and the resin are kneaded under the same transparent resin and kneading conditions as in Example 1, the average diameter of the cellulose porous structure present in the resin (referred to as "dispersion diameter" in the table)

[0218] <Example 1 to Example 20, Comparative Example 1 to Comparative Example 6>

[0219] Under the conditions of the composition, barrel temperature and kneading torque shown in Table 1, each component was charged into a twin-screw extruder (TEM58SS manufactured by SHIBAURA MACHINE CO., LTD.), kneaded, cooled and cut to obtain resin pellets (equivalent to the resin composition).

[0220] <Evaluation>

[0221] (Resin molded body)

[0222] Under the conditions of barrel temperature, mold temperature and mold holding time shown in Table 1, the resin pellets of each example were loaded into an injection molding device (manufactured by NISSEIPLASTIC INDUSTRIAL CO., LTD., NEX500) to mold ISO multi-purpose dumbbell-shaped test pieces (test part width 8 mm×thickness 4 mm×length 110 mm).

[0223] (Haze value)

[0224] The haze value of the test portion of the obtained ISO multipurpose dumbbell-shaped test piece was measured using a haze meter (TZ7700, manufactured by NIPPON DENSHOKU INDUSTRIES CO., LTD.).

[0225] (Charpy impact strength)

[0226] The obtained ISO multipurpose dumbbell-shaped test piece was subjected to A-notch processing according to the method of ISO179-1:2010.

[0227] Then, the Charpy impact strength of the processed test piece was measured at room temperature (25° C.) using an impact strength measuring device (manufactured by Toyo Seiki Seisaku-sho, Ltd., Charpy automatic impact tester).

[0228] <Materials used>

[0229] The following describes in detail the materials used.

[0230] - Raw materials for additives -

[0231] DAC (1): "Trade name CA-398-3" manufactured by Eastman Chemical Company, cellulose diacetate, number average molecular weight Mn = 15000

[0232] DAC (2): "Trade name L20" manufactured by DAICEL CORPORATION, cellulose diacetate, number average molecular weight Mn = 15000

[0233] DAC (3): "Trade name L50" ​​manufactured by DAICEL CORPORATION, cellulose diacetate, number average molecular weight Mn = 50,000

[0234] DAC (4): "Trade name L70" manufactured by DAICEL CORPORATION, cellulose diacetate, number average molecular weight Mn = 75,000

[0235] DAC(5): Cellulose diacetate synthesized by our company, number average molecular weight Mn=13000

[0236] ·TAC: "Trade name LT-35" manufactured by DAICEL CORPORATION, triacetyl cellulose, number average molecular weight Mn = 50,000

[0237] CAP: "Trade name CAP-482-20" manufactured by Eastman Chemical Company, cellulose acetate propionate, number average molecular weight Mn = 72000

[0238] ·CAB: "Trade name CAB-381-20" manufactured by Eastman Chemical Company, cellulose acetate butyrate, number average molecular weight Mn = 85,000

[0239] CNF: "BiNFIS DRY" manufactured by SUGINO MACHINE LIMITED CO., LTD., cellulose nanofiber

[0240] - Transparent resin -

[0241] PMMA: polymethyl methacrylate (manufactured by Asahi Kasei Chemicals Corporation, DELPET720V)

[0242] ·PET: Polyethylene terephthalate (manufactured by LOTTE Chemical Corporation., BCB80) ·PP: Polypropylene (manufactured by Japan Polypropylene Corporation., NOVATEC PP MG03BD) ·PS: Polystyrene (manufactured by PS Japan Corporation., GPPS-HF77)

[0243]

[0244]

[0245] As can be seen from the above results, in the present example, a resin molded body (ie, a resin composition) having higher transparency and impact strength than the comparative example can be obtained.

[0246] This embodiment includes the following aspects. (1)

[0248] A cellulose porous structure comprising at least one of cellulose and a cellulose derivative as a main component,

[0249] The specific surface area is 1m 2 / g and above and 150m 2 / g or less,

[0250] The porosity is 10% or more and 50% or less. (2)

[0252] The porous cellulose structure according to (1), wherein

[0253] When the porous cellulose structure and a resin are kneaded, the porous cellulose structure is present in the resin with an average diameter of 50 μm or less. (3)

[0255] The porous cellulose structure according to (1) or (2), wherein

[0256] The number average molecular weight of the cellulose and the cellulose derivative is 15,000 or more. (4)

[0258] The cellulose porous structure according to any one of (1) to (3), wherein

[0259] The cellulose derivative is cellulose acetate. (5)

[0261] A resin composition comprising a kneaded product containing a transparent resin and the cellulose porous structure according to any one of (1) to (4). (6)

[0263] The resin composition according to (5), wherein

[0264] The haze value of a molded body of the resin composition when the thickness is 2 mm is 15% or less. (7)

[0266] The resin composition according to (5) or (6), wherein

[0267] Charpy impact strength is 2.5 kJ / m 2 above.

[0268] The effects of the above method are as follows.

[0269] According to the invention described in (1), there is provided a cellulose porous structure comprising at least one of cellulose and a cellulose derivative as a main component, wherein the cellulose porous structure has a specific surface area of ​​less than 1 m 2 / g or more than 150m 2 / g, or a porosity of less than 10% or more than 50%, a resin molded body having high transparency and impact strength can be obtained.

[0270] According to the invention of (2), there is provided a cellulose porous structure which can obtain a resin molded body having high transparency and impact strength compared to a case where the cellulose porous structure exists in the resin with an average diameter exceeding 50 μm when the cellulose porous structure and the resin are kneaded.

[0271] According to the invention as set forth in (3), there is provided a cellulose porous structure capable of obtaining a resin molded body having higher transparency and impact strength than when the number average molecular weight of cellulose or a cellulose derivative is less than 15,000.

[0272] According to the invention as set forth in (4), there is provided a cellulose porous structure capable of obtaining a resin molded body having higher biodegradability, transparency and impact strength than when the cellulose derivative is cellulose acetate propionate.

[0273] According to the invention as claimed in (5), (6) or (7), there is provided a resin composition comprising a kneaded product comprising a transparent resin and a cellulose porous structure containing at least one of cellulose and a cellulose derivative as a main component, and a resin composition having a specific surface area of ​​less than 1 m 2 / g or more than 150m 2 / g, or a cellulose porous structure having a porosity of less than 10% or more than 50%, a resin molded body having high transparency and impact strength can be obtained.

[0274] The above-mentioned embodiments of the present invention are provided for the purpose of illustration and description. In addition, the embodiments of the present invention do not fully and exhaustively include the present invention, and do not limit the present invention to the disclosed methods. Obviously, various modifications and changes are self-evident to those skilled in the art to which the present invention belongs. The present embodiment is selected and described in order to most easily understand the principles of the present invention and its application. Thus, other technicians in the art can understand the present invention through various variations optimized for specific uses assumed to be various embodiments. The scope of the present invention is defined by the above claims and their equivalents.

Claims

1. A cellulose porous structure comprising at least one of cellulose and a cellulose derivative as a main component, The specific surface area is 1m 2 / g and above and 150m 2 / g or less, The porosity is 10% or more and 50% or less.

2. The cellulose porous structure according to claim 1, wherein When the porous cellulose structure and a resin are kneaded, the porous cellulose structure is present in the resin with an average diameter of 50 μm or less.

3. The cellulose porous structure according to claim 1 or 2, wherein The number average molecular weight of the cellulose and the cellulose derivative is 15,000 or more.

4. The cellulose porous structure according to any one of claims 1 to 3, wherein The cellulose derivative is cellulose acetate. 5 . A resin composition comprising a kneaded product containing a transparent resin and the cellulose porous structure according to claim 1 .

6. The resin composition according to claim 5, wherein The haze value of a molded body of the resin composition when the thickness is 2 mm is 15% or less.

7. The resin composition according to claim 5 or 6, wherein Charpy impact strength is 2.5 kJ / m 2 above.